2017
DOI: 10.1186/s13068-017-0890-1
|View full text |Cite
|
Sign up to set email alerts
|

Screening and evolution of a novel protist xylose isomerase from the termite Reticulitermes speratus for efficient xylose fermentation in Saccharomyces cerevisiae

Abstract: Background:The yeast Saccharomyces cerevisiae, a promising host for lignocellulosic bioethanol production, is unable to metabolize xylose. In attempts to confer xylose utilization ability in S. cerevisiae, a number of xylose isomerase (XI) genes have been expressed heterologously in this yeast. Although several of these XI encoding genes were functionally expressed in S. cerevisiae, the need still exists for a S. cerevisiae strain with improved xylose utilization ability for use in the commercial production of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…The most practical approach proposes the introduction of the pentose-utilizing capability into efficient ethanol producers such as S. cerevisiae and Z. mobilis [135,188,189]. The introduction of xylose isomerases that function well in other xylose-fermenting yeasts is the preferred solution to overcome the limitations caused by xylose to these host organisms [190,191].…”
Section: Chemicals From Hemicellulosementioning
confidence: 99%
“…The most practical approach proposes the introduction of the pentose-utilizing capability into efficient ethanol producers such as S. cerevisiae and Z. mobilis [135,188,189]. The introduction of xylose isomerases that function well in other xylose-fermenting yeasts is the preferred solution to overcome the limitations caused by xylose to these host organisms [190,191].…”
Section: Chemicals From Hemicellulosementioning
confidence: 99%
“…The corresponding positions in PirXI are distant from the active site and the mutations were not examined here. We constructed the two earlier PirXI mutants [9,14], E15D-T142S and N338C, and confirmed that the variants are beneficial for PirXI-mediated growth of strain DS75543 on d-xylose as well (Fig. 10).…”
Section: Performance Of Other Xylose Isomerase Mutantsmentioning
confidence: 60%
“…However, their properties exhibited disconnection between in vivo performance and in vitro catalytic properties. We further explored the ambiguous relation between in vivo and in vitro enzyme properties by studying PirXI mutants discovered independently in previous studies, using different S. cerevisiae host strains [9,14]. [11].…”
Section: Performance Of Other Xylose Isomerase Mutantsmentioning
confidence: 99%
See 2 more Smart Citations